EFFECT OF Nb ELEMENT CONTENT IN U-Zr ALLOY ON HARDNESS, MICROSTRUCTURE AND PHASE FORMATION - Masrukan Masrukan; M. Husna Al Hasa; Jan Setiawan; Slamet Pribadi (website, 2015)
EFFECT OF Nb ELEMENT CONTENT IN U-Zr-Nb ALLOY ON HARDNESS, MICROSTRUCTURE AND PHASE FORMATION. Experiments to determine the effect of Nb element in the U-Zr alloys on hardness, microstructure and phase formation has been done. The addition of Nb element would effect the hardness, microstructure and phase which formed. The U-Zr-Nb alloy was made with the variation of Nb 2%, 5% and 8% by melting in an electric arc melting furnace that equipped with water cooling and the argon atmosphere. The U-Zr-Nb alloy to be cut divided to some testing, such as hardness test, microstructure, and phase analysis. Hardness testing was done by Vickers hardness testing equipment, microstructure by an optical microscope, and diffraction pattern by XRD and phase analysis was done by GSAS. Hardness testing results showed that the addition of 2% to 5% Nb element in U-Zr alloys will increased in hardness, but the addition of Nb element over 5% the hardness was decreased. Observations the microstructure showed that the addition of 2% to 5%Nb element, grains were formed from fine into coarse. Phase analysis for diffraction pattern showed that the phase changed from αU and γU (Zr,Nb)at 2% Nb to be αU, γU (Zr,Nb) and δ1 (UZr2) phase at 5% and 8% Nb. Phase changes was followed by changes in its compositions. The composition of αU at 2% Nb was 40% increased to 81% at 5% Nb and decreased to 3.9% at 8% Nb. The composition of γU decreased from 59,86% to 14,91% with increased Nb from 2% to 5% and further increased to 52,74% at 8% Nb. PENGARUH KADAR UNSUR Nb PADA PADUAN U-Zr-Nb TERHADAP SIFAT MEKANIK, MIKROSTRUKTUR DAN PEMBENTUKAN FASA. Percobaan untuk mengtahui pengaruh kadar Nb pada paduan U-Zr-Nb terhadap sifat mekanik, mikrostruktur dan pembentukan fasa telah dilakukan. Penambahan unsur Nb diduga akan mempengaruhi sifat mekanik, mikrosruktur, ketahanan korosi dan fasa yang terbentuk. Penambahan unsur Nb ke dalam paduan U-Zr dimaksudkan untuk memperluas daerah fasa gamma yang stabil dan memperbaiki ketahanan korosi. Mula-mula dibuat paduan U-Zr-Nb pada variasi Nb 2%, 5% dan 8% dengan cara melebur di dalam tungku peleburan busur listrik yang berpendingin air dan dalam media gas argon. Paduan U-Zr-Nb yang terbentuk dipotong-potong untuk dikenai beberapa pengujian, diantaranya uji mekanik (kekerasan), mikrostrutur, dan fasa yang terbentuk. Pengujian kekerasan dilakukan dengan menggunakan peralatan uji kekerasan Vickers, mikrostruktur dengan menggunakan mikroskop optik, dan fasa dengan menggunakan XRD. Hasil pengujian kekerasan menunjukkan bahwa penambahan Nb pada paduan U-Zr dari 2% menjadi 5% mengakibatkan kenaikan kekerasan, tetapi kemudian kekerasan turun pada penambahan di atas 5% Nb. Pengamatan mikrostruktur yang terbentuk memperlihatkan bahwa pada penambahan unsur Nb sebesar dari 2% menjadi 5% maka terbentuk butir dari kasar menjadi halus. Dilihat dari pembentukan fasa, terjadi perubahan yakni dari αU dan γU pada 2% Nb menjadi fasa αU, γU dan δ1 (UZr2) pada 5% Nb dan 8% Nb. Perubahan fasa tersebut juga diikuti dengan perubahan prosentase fasa yaitu pada 2% Nb, dimana fase αU yang semula 40% mengalami kenaikan menjadi 81% pada 5% Nb dan selanjutnya turun menjadi 3,9% pada 8% Nb. Untuk fasa γU terjadi penurunan yang semula 59% menjadi 14% pada 5% Nb dan selanjutnya naik menjadi 32 % pada 8% .